Vortex Dynamics Theories and Applications - Harun, Zambri (IntechOpen, 2020)
The book comprises of different areas in which vortex dynamics is important, its generation, evolution, interactions with other motions, and finally the ways it can be controlled. Vortex characteristics are important in many aspects of our lives, from blood circulation in the arteries to the high-speed jet. Flow control and manipulation of vortices have been used to reduce drag for large tankers resulting in billions of dollars in savings. An effective smoke management system must be put in place for critical areas to ensure the safety of people, for example in a very large shopping complex or a large airport. Advanced computational and cloud-computing facilities have contributed significantly to large-scale simulation projects. Therefore, validations could be performed for larger windows of study so that it can now cover the entire e.g. central business district (CBD) for urban heat island (UHI) study or land-ocean interactions.